PENINGKATAN PENJUALAN UMKM MELALUI PRODUCT BRANDING DI DESA BINTAN BUYU - Sambodo, Bambang; Marlinda, Charly; Utami, Ranti; Kurnia, Sri; Santoso, Nanda Kristia; Friassantano, Risgar; Lase, Erni Wati; Jacky, Jacky; Jillyana, Marcelia; Rotuah.S, Ricky Marthin; Reformeizi, Muhammad Wahyu; Murniati, Yulis (Jurnal Pengabdian, Pembelajaran dan Pemberdayaan Ekonomi Masyarakat (JP3EM), 2025)
This research reviews the increase in MSME sales through product branding. This study aims to illustrate how important branding is for MSME actors. This research uses qualitative research to explain the brand's contribution to MSMEs. The research instruments are observations, interviews, the source of this research data is the results of interviews from MSME actors in Bintan Buyu Village. The result of the research is that the brand has proven to be effectively able to increase turnover in 2 MSME actors who are used as objects in this community service program.